Fetomaternal outcome in women with hemolysis, elevated liver enzymes and low platelet count syndrome: a retrospective study - Divya, M. B.; Kondakasseril, Nishi Roshini; Andrews, Mekkattukunnel Andrews (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: HELLP (hemolysis, elevated liver enzymes and low platelet count) syndrome which is a variant form of severe preeclampsia is an important cause of maternal and fetal mortality and morbidity. The importance lies in the early diagnosis and timely intervention for better fetal and maternal outcome. The objective of this study was to assess the maternal and fetal outcome in pregnancies complicated with HELLP syndrome. Methods: This is a retrospective study analyzing fetomaternal outcome in 63 women diagnosed with HELLP syndrome in the department of obstetrics and gynecology, Government Medical College, Thrissur from 1st January 2014 to 31st December 2016. Details were collected from data records library. Results: Among 7,566 deliveries, 63 women (0.83%) had HELLP syndrome. Mean age was 29.5 years. 47.6% (n=30) women developed HELLP syndrome at gestational age less than 34 weeks. Maternal complications were abruption (27.78%), acute kidney injury (16.67%), DIC (16.67%), sepsis (11.11%) and postpartum hemorrhage (11.11%). In this study, HELLP syndrome lead to one maternal death (1.58%). The perinatal mortality was 25.75%. Conclusions: HELLP syndrome is an alarming complication, which brings high maternal and perinatal morbidity and mortality.